Efek Aplikasi Pupuk NPK cair terhadap P-tersedia, Serapan P, dan Bobot Umbi Bawang Merah (Allium ascalonicum L.) di Tanah Inceptisol Jatinangor - Sara, Dirga Sapta; Sofyan, Emma Trinurani; Citraresmini, Ania (Soilrens, 2024)
Shallots are a high-value horticultural commodity that requires optimal phosphorus (P) availability tosupport growth and bulb production. However, Inceptisol soils have limitations in providing phosphorusdue to their high fixation capacity and low organic matter content. This study aimed to examine the effectof liquid NPK fertilizer application on soil phosphorus availability, plant phosphorus uptake, and shallotbulb yield in Inceptisol soil. The experiment was conducted using a randomized complete block design(RCBD) with six treatments: control, recommended NPK fertilizer, and four doses of liquid NPK fertilizer(½, 1, 1 ½, and 2 doses), each with four replications. The results showed that liquid NPK fertilizerapplication significantly increased soil phosphorus availability, plant phosphorus uptake, and both freshand dry bulb weights compared to the control. The 1 ½-dose liquid NPK fertilizer treatment resulted in anavailable P content of 12.72 ppm, a phosphorus uptake of 3.28 mg plant⁻¹, a fresh bulb weight of 78.63 gclump⁻¹, and a dry bulb weight of 63.86 g clump⁻¹, which were not significantly different from therecommended NPK treatment. This indicates that applying 1 ½ doses of liquid NPK fertilizer can serve asan equivalent alternative to conventional granular NPK fertilizer in providing phosphorus for shallotcultivation. Thus, the application of liquid NPK fertilizer at 1 ½ times the recommended dose can beproposed as an effective and efficient fertilization strategy to improve shallot productivity in Inceptisol soil.